Wednesday

April 16, 2014

April 16, 2014

Posted by **sooto** on Tuesday, February 20, 2007 at 8:30pm.

Your equations:

-3x + y = -5

x + 2y = 0

Let's solve the second equation for x:

x = -2y

Now let's substitute -2y for x in the first equation to solve for y:

-3(-2y) + y = -5

6y + y = -5

7y = -5

y = -5/7

Now let's substitute -5/7 for y in the second equation to solve for x:

x + 2(-5/7) = 0

x + -10/7 = 0

x = 10/7

Check these values with the original equations. It always helps to check your work!

I hope this will help.

**Related Questions**

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...

HELP! - The problem using elimination/substitution methods what is the solution ...

derivative - I am finding the second derivative of (x^2)(y^3) = 1 2x(y^3) + (x^2...

maths - use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 ...

Expressions help - I have no idea on how to do this equation please help me. ...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

algebra - needing help with is problem solve for x: 3x-2y=-6 here is my solution...

algebra - A. 3x + y = 8 x-y =6 B. x- 1/2y =2 y=2x-4 C. x + 2y = 9 2y = -x + 13 I...

Pre Cal.--Check my work? - Solve the system of equations: x - y - z = 2; x + 2y...

Algebra - What is the standard form of the equation of the line passing through ...